DERAJAT KECEMASAN PASIEN DENGAN RASA NYERI PASCA PENCABUTAN GIGI P2 PADA PERAWATAN ORTHODONTIK CEKAT DI KLINIK FRESH DENTAL YOGYAKARTA - Vifi Kurniawati; Siti Sulastri; Dwi Suyatmi (Poltekkes Kemenkes Yogyakarta, 2014)
One of the consequences of tooth extraction is pain due to damage from hardand soft tissue. Besides the revocation itself, the quality of pain is influenced by thedegree of patient anxiety. Anxiety is an affective psychological factors that affectpain perception. Patients were tense and anxious feeling more pain than patientsrelax.To determine the relationship between the degree of anxiety of patients withpain after tooth extraction fixed orthodontic treatment P2 at Fresh Dental Clinic inYogyakarta.This study uses an analytical survey, with a crosssectional approach.The research sample using sampling techniques pusposive selected number of respondentswere 30. Measuring the degree of anxiety by using a questionnaire, whilethe pain was measured using a pain questionnaire sheet. Analysis of data usingspearmant rank test.Respondents were most respondents with high levels of anxietyas many as 15 people (50%). The pain after tooth extraction P2 Fresh Dental Clinicin Yogyakarta are in the weight category of 18 people (60%). there is a relationshipinfluences the degree of anxiety with pain after tooth extraction p2 at Fresh Dentalclinic in Yogyakartawith a significance value of Á value 0.000 <0.05.There is a significantrelationship between the degree of anxiety of patients with pain after tooth extractionP2 at fixed orthodontic treatment at Fresh Dental clinic in Yogyakarta with asignificance value 0.000 <0.05.